2016
DOI: 10.1037/pas0000262
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing the “traditional background hypothesis” for elevated MMPI and MMPI-2 Lie-scale scores.

Abstract: The Lie (L) scale of the Minnesota Multiphasic Personality Inventory (MMPI) is widely regarded as a measure of conscious attempts to deny common human foibles and to present oneself in an unrealistically positive light. At the same time, the current MMPI-2 manual states that "traditional" and religious backgrounds can account for elevated L scale scores as high as 65T-79T, thereby tempering impression management interpretations for faith-based individuals. To assess the validity of the traditional background h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…One limitation of this study was that we were not able to determine the level of absolute degree of strength of faith in the Muslim religion, only whether increasing levels of faith, as measure by the MMS, were associated with increasing L-r scale scores, because there is no normative data for the MMS. It is important to note, however, that in the Rosen et al (2016) meta-analysis, the only evidence for strength of religious belief is that the participants had applied for and were members or students of a seminary or rabbinical school.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One limitation of this study was that we were not able to determine the level of absolute degree of strength of faith in the Muslim religion, only whether increasing levels of faith, as measure by the MMS, were associated with increasing L-r scale scores, because there is no normative data for the MMS. It is important to note, however, that in the Rosen et al (2016) meta-analysis, the only evidence for strength of religious belief is that the participants had applied for and were members or students of a seminary or rabbinical school.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent meta-analytic study, Rosen, Baldwin, and Smith (2016) examined the viability of the TBH by comparing MMPI-2 L scale elevations in study samples presumed to reflect strong Christian (and Judeo) faith–based values and behaviors relative to the MMPI-2 normative sample. Consistent with their hypothesis, Rosen et al reported that the overall the average L scale elevation was 0.50 SD greater than that of the normative sample.…”
mentioning
confidence: 99%
“…Of more salience for interpretive purposes are the candidate validity scales, where the L and K scale scores above 60 suggest some degree of defensiveness or general impression management concerns, as would be expected in the context of a psychological assessment. They may also reflect the influence of participants' conservative religious background, which as we discuss below has been particularly studied with regard to scale L (Duris, Bjork, & Gorsuch, 2007;Rosen, Baldwin, & Smith, 2016). Regardless of the source of these elevations, such scores on L and K should be con- Note: Respective group sizes were 606 and 154 for married and single women.…”
Section: Discussionmentioning
confidence: 97%
“…Previous reports made the following observations regarding L score: Drivers who have had a large-scale accident have higher L scores than those who have not had a large-scale accident;[ 7 ] patients placed in prison have high L scores;[ 8 ] policemen with high L scores at the time of examination for service tend to cause problems in the future;[ 9 ] and religious teaching (virtue) increases L score. [ 10 ] Another past study reported that individuals with very high L scores tend to show displeasure with surgery results, or to be “doctor shoppers”. [ 11 ] Namely, L score is used not to detect the credibility of the answer, but rather as an index that shows these individuals intentionally try to make themselves look better in the eyes of others.…”
Section: Discussionmentioning
confidence: 99%